Publication-Driven Research Experience for Undergraduates (REU) Program in Optics and Photonics in the Philippines Using Circuit Analogue-Based Research Experiments - Dingel, Benjamin (Archīum Ateneo, 2021)
We summarize a unique publication-driven Research Experience for Undergraduates program in optics/photonics that uses electronic circuit analogue-based research to strengthen students’ engagement in research. At present, we have published 4 journal and conference papers.